Competition in Inflection and Word-Formation - Rainer, Franz; Gardani, Francesco; Dressler, Wolfgang U.; Luschützky, Hans Christian (Studies in Morphology, 2019)
This is the first volume specifically dedicated to competition in inflection and word-formation, a topic that has increasingly attracted attention. Semantic categories, such as concepts, classes, and feature bundles, can be expressed by more than one form or formal pattern. This departure from the ideal principle "one form - one meaning" is particularly frequent in morphology, where it has been treated under diverse headings, such as blocking, Elsewhere Condition, Pāṇini's Principle, rivalry, synonymy, doublets, overabundance, suppletion and other terms. Since these research traditions, despite the heterogeneous terminology, essentially refer to the same underlying problems, this volume unites the phenomena studied in this field of linguistic morphology under the more general heading of competition. The volume features an extensive state of the art report on the subject and 11 research papers, which represent various theoretical approaches to morphology and address a wide range of aspects of competition, including morphophonology, lexicology, diachrony, language contact, psycholinguistics, sociolinguistics and language acquisition.